Aerospace Environmental Health: Considerations and Countermeasures to Sustain Crew Health Through Vastly Reduced Transit Time to/From Mars - Sobel, Annette; Duncan, Robert (Frontiers in Public Health, 2020)
The concept of implementation of environmental health protection and sustainment in aerospace environments by definition implies a One Health systems approach. One Health indicates an inherently complex, contextually interrelated system with consideration of human, animal, plant, systems engineering, and environmental health, their interrelationships and networks. One Health implies seamless integration of sub-system co-dependencies to achieve an outcome of overall health protection for the individual. This general overview will address the critical components of space environmental health in anticipation of increasing duration and interaction of human, animal and plant habitation of aerospace and extreme environments into the future. Of many considerations to be addressed, precision medicine and bioinformatics are the most rapidly evolving. Complex interdependencies will emerge from macro- and micro- environmental ecosystems data analysis, not yet fully comprehended, or understood in the context of space health. We will conclude this contribution with suggested new countermeasures strategies to protect space crew through mitigation of radiation exposure in flight.